2009
DOI: 10.1055/s-0029-1224173
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Fatness and Fitness on CVD Risk Factors in Asian Youth

Abstract: The purpose of this study was to investigate the effects of fatness and fitness on insulin resistance (IR) and cardiovascular disease (CVD) risk factors among Korean adolescents. A total of 322 male high school students participated Departme nt of Sport and Leisure Studies, Yonsei University, Seoup, Republic of Korea Department of Sport and Leisure Studies, Yonsei University, Seoup, Republic of Korea in the cross-sectional part of the study. To determine the interaction of fatness and fitness levels on IR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
2
15
0
2
Order By: Relevance
“…This indicates a need to encourage individuals to participate in low and moderate physical activity to manage MetS. According to many previous studies, physical activity is somewhat important in preventing chronic diseases such as type 2 diabetes and cardiovascular disease (Jekal et al, 2009). Previous studies have also observed that mild or moderate exercise had a more significant effect on reducing the prevalence of MetS and cardiovascular risk factors (Lakka & Laaksonen, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a need to encourage individuals to participate in low and moderate physical activity to manage MetS. According to many previous studies, physical activity is somewhat important in preventing chronic diseases such as type 2 diabetes and cardiovascular disease (Jekal et al, 2009). Previous studies have also observed that mild or moderate exercise had a more significant effect on reducing the prevalence of MetS and cardiovascular risk factors (Lakka & Laaksonen, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…And BMI was only correlated with sit-and-reach tests in boys (36) . It has been shown there were interactions between fatness and fi tness on CVD risk factors in Asian youth (37) . Therefore, based on the tree structure point of view, our study results may imply that the combination of poor fl exibility and body composition in male adolescent may worsen and contribute to the metabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena have been reported in Japanese children [10][11][12] . Furthermore, in previous cross-sectional studies, the risk for MetS has been reported to be associated with fatness and aerobic fitness in European 13) , American 14) , Canadian 15) , Australian 16) , and Asian children [17][18][19] .…”
Section: Introductionmentioning
confidence: 91%